Structural changes in South Korea employment (2000-2021) - Minki Hong (European Commission, Joint Research Centre (JRC), 2023)
Using a job-based methodology, this paper studies structural shifts in employment in the South Korean labor market from 2000 to 2021. The methodology follows the approach suggested and applied in the reports published in the context of the European Jobs Monitor, such as Eurofound (2015, 2017). This study segments the analysis duration into three periods: 2000-2009, 2009-2019, and 2019-2021. The patterns of change in the employment structure between 2000-2009 and 2009-2019 varies greatly. Employment in higher-paid jobs increased between 2000 and 2009. Employment polarization, on the other hand, emerged between 2009 and 2019. Since 2000, changes in the employment structure have been influenced by a combination of increasing demand for highly skilled labor, deindustrialization, increased trade, and changes in the employment protection system. As the population ages rapidly in the 2010s, employment in health and social work services is increasing rapidly. The 2019-2021 period was set aside to investigate the impact of COVID-19 on the employment structure. Due to the spread of COVID-19, employment in face-to-face education and food services decreased in 2020 but quickly recovered in 2021.
Keywords: 330; employment; occupational change; polarization; jobs approach; economic restructuring